Effects of thermal and diffusion phase-lags in a plate with axisymmetric heat supply. Issue 2 (8th August 2016) - Kumar, Rajneesh; Sharma, Nidhi; lata, parveen
Abstract : Purpose: The purpose of this paper is to depict the effect of time and thermal and diffusion phase lags due to axisymmetric heat supply in a ring. The problem is discussed within the context of DPLT and DPLD models. The upper and lower surfaces of the ring are traction free and subjected to an axisymmetric heat supply. Design/methodology/approach: The solution is found by using Laplace and Hankel transform technique and a direct approach without the use of potential functions. The analytical expressions of displacements, stresses and chemical potential, Temperature and mass concentration are computed in transformed domain. Numerical inversion technique has been applied to obtain the results in the physical domain. Numerically simulated results are depicted graphically. The effect of time and diffusion and thermal phase-lags are shown on the various components. Some particular cases of result are also deduced from the present investigation. Findings: it is observed that change in time changes the behavior of deformations of the various components of stresses, displacements, chemical potential function, temperature change and mass concentration. We find that for t=0.2, trends are oscillatory in all the cases whereas for t=0.1, trends are quite different. A sound impact of diffusion and thermal phase-lags on the various quantities is observed. A lot of difference in the trends of Single phase lag and Dual phase lag is observed. The use of diffusion phase-lags in the equation of mass diffusion gives a more realistic model of thermoelastic diffusion media as it allows a delayed response between the relative mass flux vector and the potential gradient Originality/value: This problem is totally new because dual phase lag is applied in heat conduction and diffusion equation while considering the problem of plate in axisymmetric heat-supply.